EFEK GASTROPROTEKTIF EKSTRAK ETANOL BUAH LABU KUNING (Cucurbita moschata (Duch.) Poir) PADA TIKUS JANTAN GALUR WISTAR YANG DIINDUKSI ASPIRIN - Maulida Shofiatun; Ririn Lispita Wulandari (Universitas Wahid Hasyim Semarang, 2020)
ABSTRACT Non-steroidal anti-inflammatory drugs (NSAIDs) can cause side effects of gastric ulcers. Based on previous research, it is known that pumpkin contains flavonoids which can protect the gastric mucosa. The aim of this study was to determine the gastroprotective effect of ethanol extract of Cucurbita moschata (Duch.) Poir fruit in male rats Wistar-induced by aspirin. The study used a randomized matched posttest only control group design. Cucurbita moschata (Duch.) Poir fruit extraction was carried out by ultrasonic method. A total of 24 rats were divided into 6 groups: normal control (CMC Na 0,5%; ulcer control (CMC Na 0,5%); positive control (ranitidine HCl 10 mg/kg BW); treatment group (Cucurbita moschata (Duch.) Poir fruit ethanol extract at dose of 100, 200, and 400 mg/kg BW). Treatments lasted for 14 days. One hour after administering the test solution on the 14th day, all rats were given 200 mg/kg BW of aspirin (except normal controls) orally, then fasted for 12 hours. On the 15th day, all rats were sacrificed, dissected and their stomachs were taken. Gastric histology preparations were made with hematoxylin-eosin staining, microscopically read, discussed the number and severity of ulcers. Both data were processed and analyzed by Kruskal Wallis and Mann Whitney (95% confidence level). The results showed that the administration of EEBLK doses of 100, 200, and 400 mg/kg BW resulted in a score of the number and severity of ulcers that were lower significantly than of ulcer controls (p